2022
DOI: 10.21608/mjmr.2022.251366
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of Central Nervous System Fetal Malformations in patients attending Fetomaternal Unit Minia University as an observation study

Abstract: Background: Central nervous system (CNS) anomalies are the most serious congenital abnormalities. Ultrasound examination is an effective and non-invasive modality for prenatal diagnosis of these anomalies. The objectives of this study were to detect the proportion of C.N.S malformations in patients attending the feto-maternal unit at Minia University and analyze the related factors at 22nd to 28th weeks of gestation and detect the diagnostic accuracy of Ultrasound in the diagnosis of CNS malformations. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Hassan et al (2022) (9) reported that, as regarding ultrasound detected CNS anomalies in 79 fetuses. The most common anomaly detected wasVentriculomegaly that found in 22%.…”
Section: Prevalence Of Neurological Congenital Anomalies In Sohag Gov...mentioning
confidence: 98%
See 4 more Smart Citations
“…Hassan et al (2022) (9) reported that, as regarding ultrasound detected CNS anomalies in 79 fetuses. The most common anomaly detected wasVentriculomegaly that found in 22%.…”
Section: Prevalence Of Neurological Congenital Anomalies In Sohag Gov...mentioning
confidence: 98%
“…It is important to determine whether the CNS structures present complex embryology and anatomy because the CNS undergoes most of its changes during gestation. CNS changes are associated with changes in the US aspects of the CNS during gestation (9) . Therefore, every professional involved in the fetal evaluation should be aware of the embryology and anatomy of CNS as well as of its ultrasound characteristics of different gestational ages to avoid diagnostic errors (9) .…”
Section: Prevalence Of Neurological Congenital Anomalies In Sohag Gov...mentioning
confidence: 99%
See 3 more Smart Citations